Ensuring Legal Certainty for Customary Law Communities in Indonesia: Analyzing the Ratification Process of the Customary Law Communities Bill - Zainurohmah, Zainurohmah; Salim Noer Mahmudi; Jihan Alfarisi (Contemporary Issues on Interfaith Law and Society, 2024)
This study examines the pursuit of legal certainty for customary law communities in Indonesia through analyzing the ratification process of the Customary Law Communities Bill. Customary law communities, integral to Indonesia's cultural fabric, have long grappled with ambiguous legal recognition, leading to vulnerability and uncertainty.  By scrutinizing the journey of the Customary Law Communities Bill towards enactment, this research aims to elucidate the prospects of establishing a robust legal framework safeguarding the rights and interests of these communities. Drawing from legislative documents, legal debates, and stakeholder insights, the study assesses the bill's opportunities and challenges. Additionally, the research delves into the implications of legal certainty for customary law communities, exploring its potential impact on autonomy, cultural heritage, and socio-economic development. Through case studies and empirical evidence, the study illuminates the practical ramifications of the bill's provisions across Indonesia. This study contributes to discussions on legal pluralism, indigenous rights, and community empowerment in Indonesia. By advocating for the recognition and protection of customary law communities within the legal framework, it seeks to foster inclusive governance and cultural diversity. Ultimately, it underscores the significance of ensuring legal certainty as a cornerstone of justice and equality for all communities, irrespective of their cultural or legal traditions.